Turk J Gastroenterol 2022
DOI: 10.5152/tjg.2022.21827
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary Management of Pediatric Hepatoblastoma: A 20-Year Single-Center Experience

Abstract: Background: Hepatoblastoma is rare cancer that responds well to risk-based chemotherapy, and surgical treatment is needed to achieve complete remission and satisfactory survival rates in hepatoblastoma patients. In this study, we evaluated the clinical features and treatment outcomes of pediatric hepatoblastoma patients treated in our clinic. Methods: Eighteen patients with hepatoblastoma who were treated and followed up in our center between June 1999 and June 2020 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Recent advancements in therapy have resulted in notable enhancements in the prognosis of pediatric patients diagnosed with HB. Integrating surgical and chemotherapeutic interventions has yielded noteworthy 5-year overall survival (OS) and disease-free survival rates, attaining 88.9% and 80.8%, respectively ( 5 , 6 ). The achievement of total elimination of liver tumors is of utmost importance in ensuring the efficacy of the treatment ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advancements in therapy have resulted in notable enhancements in the prognosis of pediatric patients diagnosed with HB. Integrating surgical and chemotherapeutic interventions has yielded noteworthy 5-year overall survival (OS) and disease-free survival rates, attaining 88.9% and 80.8%, respectively ( 5 , 6 ). The achievement of total elimination of liver tumors is of utmost importance in ensuring the efficacy of the treatment ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Conversely, 2%-33% of children with HBL still require LT for complete resection. [9][10][11][12][13] A recent analysis of the National Cancer Database showed that 23% of children with HBL managed at Commission on Cancer US hospitals are not offered any type of surgical treatment. 14 Although total hepatectomy and LT is the only potentially curative option ensuring complete tumor extirpation in many children with unresectable HBL, LT was not considered a feasible treatment modality until the surge of publications showing favorable survival after LT between 1999 and 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Data suggest that about 10%–30% of children with HBL that undergo non‐transplant liver resection will have disease recurrence 6–8 . Conversely, 2%–33% of children with HBL still require LT for complete resection 9–13 . A recent analysis of the National Cancer Database showed that 23% of children with HBL managed at Commission on Cancer US hospitals are not offered any type of surgical treatment 14 …”
Section: Introductionmentioning
confidence: 99%
“…Hepatoblastoma (HB) is the most common primary liver malignancy in children [1][2][3][4], with increasing incidence in the United States [2,3,5]. It is most frequently diagnosed in children younger than 3 years of age [6]. The staging system for HB is based on pretreatment extent of disease or PRETEXT staging.…”
Section: Introductionmentioning
confidence: 99%